ROLES OF MOTHER IN EMMA DONOGHUE’S NOVEL ROOM - Muhammad Fadil Citra; Sri Wulan (JOURNAL OF LANGUAGE, 2022)
This study focuses on the roles of mother performed by Ma in the novel Room. The purpose of this research is to show Ma's dominant roles in educating, maintaining, and managing the life of Jack, her son. The descriptive qualitative method was applied to analyze the data and to answer the research problems in this study. The data are obtained from the quotations in the novel Room. This research is analyzed based on a theory of the roles of mother proposed by several experts such as Ki Hajar Dewantara in Muthmainnah, McGuigan, and Good. Twelve data could be used as evidences of the mother's roles represented by Ma. The results of the study show that there are four dominant roles of mother performed by Ma. The four roles of a mother in the novel are mother as an educator, mother as a carer of family's physical and mental health, mother as a company, and mother as a communicator. From the data presented in the analysis, it is very clear that Ma performs her roles as a mother well. With limited space for movement, Ma can still provide education, health maintaining, attention and affection, play and guide for Jack through life.